2000
DOI: 10.1016/s0006-3495(00)76683-5
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Cloning of cDNA Encoding a Drosophila Ryanodine Receptor and Functional Studies of the Carboxyl-Terminal Calcium Release Channel

Abstract: Ryanodine is a plant alkaloid that was originally used as an insecticide. To study the function and regulation of the ryanodine receptor (RyR) from insect cells, we have cloned the entire cDNA sequence of RyR from the fruit fly Drosophila melanogaster. The primary sequence of the Drosophila RyR contains 5134 amino acids, which shares approximately 45% identity with RyRs from mammalian cells, with a large cytoplasmic domain at the amino-terminal end and a small transmembrane domain at the carboxyl-terminal end.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
53
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(55 citation statements)
references
References 33 publications
2
53
0
Order By: Relevance
“…The five types of conserved domain (Figure 3) in the N-terminal region of BdRyR included: a mannosyltransferase, IP3R and RyR domain (MIR, pfam02815) at position 211-392; two RyR and IP3R homology domains (RIH, pfam01365) at positions 439-648 and 2227-2456; three spore lysis The C-terminal region of RyR protein can form functionally important domains shared by mammalian and insect RyRs [9,20]. Thus, the C-terminal region of BdRyR was compared with other reported insect RyRs, including DmRyR from D. melanogaster, sRyR from B. mori, PxRyR from P. xylostella, and NlRyR from N. lugens (Figure 4).…”
Section: Conserved Structural Domains In Bdryrmentioning
confidence: 99%
See 1 more Smart Citation
“…The five types of conserved domain (Figure 3) in the N-terminal region of BdRyR included: a mannosyltransferase, IP3R and RyR domain (MIR, pfam02815) at position 211-392; two RyR and IP3R homology domains (RIH, pfam01365) at positions 439-648 and 2227-2456; three spore lysis The C-terminal region of RyR protein can form functionally important domains shared by mammalian and insect RyRs [9,20]. Thus, the C-terminal region of BdRyR was compared with other reported insect RyRs, including DmRyR from D. melanogaster, sRyR from B. mori, PxRyR from P. xylostella, and NlRyR from N. lugens (Figure 4).…”
Section: Conserved Structural Domains In Bdryrmentioning
confidence: 99%
“…In birds, amphibians and fish, two RyRs, RyRA and RyRB are homologous to mammalian RyR1 and RyR3, respectively [17][18][19]. In contrast to mammals, only one gene encoding a RyR is present in Drosophila melanogaster, and it shares a 44 to 46% amino acid identity with the RyR mammalian isoforms [20]. Interestingly, mammalian and insect RyRs are more different in sequence than their corresponding inositol trisphosphate receptors (InsP3Rs), which may make RyRs better targets for insecticidal molecules with low mammalian toxicity.…”
Section: Introductionmentioning
confidence: 99%
“…Third, the role of ryanodine receptor (RyR)-mediated release from intracellular Ca 2ϩ stores was also examined. Ryanodine, at micromolar concentrations (Sutko et al 1997), is a selective inhibitor for RyRs and has been shown to be effective in a variety of invertebrates, including Aplysia, Hirudo, and Drosophila (Geiger and Magoski 2008; Trueta et al 2004;Xu et al 2000). Application of ryanodine (50 M) in conjunction with the pairing protocol blocked LTP [ryanodine ϩ pairing, 102 Ϯ 9%, n ϭ 10; ryanodine control, 93 Ϯ 9%, n ϭ 11; P Ͻ 0.05; F (8,68) ϭ 10.898, P Ͻ 0.001; Fig.…”
Section: Pairing-induced Potentiation Requires An Increase In Postsynmentioning
confidence: 99%
“…5 Therefore, insect RyR is a potential target for new insecticides. 6 The molecular target of some new synthetic insecticides, flubendiamide and anthranilic diamide, was shown to be RyR.…”
Section: Introductionmentioning
confidence: 99%